Transcriptome characterization and expression analysis related to sex‐determining genes in Chilo sacchariphagus (Lepidoptera Crambidae), a key pest of sugarcane. Issue 2 (10th February 2022) - Liu, Jianbai; Wu, Han; Yi, Jiequn; Li, Jihu; Cheng, Yinjie; Zhang, Yifei; Sun, Donglei; An, Yuxing
Abstract: Chilo sacchariphagus is one of the most harmful pests of sugarcane, sorghum, corn, and other crops, in China and other countries and regions. In order to elucidate the molecular mechanisms involved in the sexually dimorphic development of C. sacchariphagus, transcriptome data of female and male adults were obtained. A total of 127, 812, 174 and 126, 593, 664 clean reads of males and females were arranged into 45, 693 and 37, 034 unigenes for males and females, respectively, 26, 949 of which were annotated. Candidate genes involved in sexual development were identified and analysed. Statistical analysis revealed that 18, 642 genes were differentially expressed in females and males, 9, 307 of which were up‐regulated in males and 9, 335 of which were up‐regulated in females. As indicated by GO classification, DEGs were mainly involved in cell part, cellular process and binding. KEGG enrichment analysis showed that 6, 037 DEGs were assigned to 295 metabolic pathways. Based on annotation and transcriptome data, we identified twenty‐two sex determining genes, of which Csactra2, Csacemc, Csacfru, Csacix, Csacovo, CsacdsxM, and Csacsxl showed a higher expression in males than that in females, while CsacgroX4, Csacfem, CsacgroX9, Csacmsl1, Csacmsl2, Csacmsl3, Csacotu, Csacvir, Csacrunt, and CsacdsxF were more highly expressed in female. In addition, Csactra2 and CsacgroX9 were enriched in Spliceosome, Notch signaling, and Wnt signaling pathways, respectively. And the pathways are crucial in regulating insect growth, differentiation and development. This transcriptome study provides rich and significant information regarding the genes involved in sex differentiation and determination, which would improve our understanding of the molecular mechanisms related to sex determination and be helpful for providing the basis for a wide spectrum of strategies to benefit pest control and prevention, and agriculture and public health.